Alternative energy prospects : with particular reference to Jamaica. - Wright, Raymond M. (1991)
Points out that energy conservation is the most effective form of 'alternative energy' and will increase the energy available to all countries at the lowest cost. There is need to initiate public policy measures that will successfully promote greater energy efficiency, through, for example, incentives, persuasion, penalties, subsidies and taxes.